2012
DOI: 10.2174/1874213001205010045
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Antifungal Wheat has no Detrimental Effects on the Key Soil Species Lumbricus terrestris

Abstract: Abstract:Since the first introduction of genetically engineered (GE) plants, one of the major concerns has been their potential effects on non-target organisms and ecosystem services. We focused in this study on the earthworm species Lumbricus terrestris as important ecosystem engineer and studied its performance when feeding on GE antifungal wheat. We compared litter consumption, weight change and mortality of individuals feeding on GE wheat with either specific resistance against powdery mildew (Blumeria gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These results indicated that transgenic crops containing a viral gene conferring resistance to viral disease had little effect on soil microbial diversity (excluding a small number of studies) compared with non-transgenic crops. Transgenic wheat also had no adverse effects on soil biological indicators, such as Folsomia candida [47] and earthworm [48]. Duc et al found that GM wheat with race-specific antifungal resistance against powdery mildew (Pm3b), and two with nonspecific antifungal resistance, had no impact on the soil fauna community (mites, springtails, annelids, and diptera).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that transgenic crops containing a viral gene conferring resistance to viral disease had little effect on soil microbial diversity (excluding a small number of studies) compared with non-transgenic crops. Transgenic wheat also had no adverse effects on soil biological indicators, such as Folsomia candida [47] and earthworm [48]. Duc et al found that GM wheat with race-specific antifungal resistance against powdery mildew (Pm3b), and two with nonspecific antifungal resistance, had no impact on the soil fauna community (mites, springtails, annelids, and diptera).…”
Section: Discussionmentioning
confidence: 99%